KEWENANGAN PENENTUAN STATUS GANGGUAN JIWA PADA PELAKU TINDAK PIDANA DALAM PROSES PENYIDIKAN - David Hendra; Indra Afrita; Tri Anggara Putra (Collegium Studiosum Journal, 2025)
The determination of mental disorder status of criminal offenders constitutes a crucial aspect in the investigation process, as it directly relates to criminal responsibility and the protection of human rights. In the investigative practices of the Criminal Investigation Unit (Satreskrim) of Pekanbaru City Police, investigators’ authority in determining the mental condition of suspects often encounters normative and practical limitations, particularly in coordination with medical professionals and mental health institutions. This study aims to analyze the authority of investigators in determining the mental disorder status of criminal offenders and to examine its implementation during the investigation process. This research employs a sociological legal research method, using an empirical approach that views law as social behavior. Data were collected through literature review of statutory regulations and criminal law doctrines, as well as interviews with investigators of Satreskrim Polresta Pekanbaru and related parties. The findings indicate that investigators do not possess the authority to independently determine a suspect’s mental disorder status; such determination must be conducted by authorized medical professionals upon the investigator’s request. However, in practice, several obstacles persist, including limited facilities, complex administrative procedures, and insufficient understanding among suspects and their families regarding psychiatric examination processes. Therefore, regulatory strengthening, enhanced inter-sectoral coordination, and capacity building for investigators are necessary to ensure legal certainty, justice, and the protection of human rights in the investigation process.